Systematics and biogeography of Berberis s.l. inferred from nuclear ITS and chloroplast ndhF gene sequences. Issue 1 (9th February 2015) - Adhikari, Bhaskar; Milne, Richard; Pennington, R. Toby; Särkinen, Tiina; Pendry, Colin Alistair
Abstract: Berberis is the largest genus in the Berberidaceae, comprising more than 500 species. It is now recognised to include all of the compound‐leaved species formally ascribed to Mahonia, as well as simple‐leaved species comprising Berberis s.str. Berberis s.l. has a mainly Northern Hemisphere distribution, with a centre of diversity in the Sino‐Himalaya region, while Berberis s.str. extends into South America where it has a secondary centre of diversity. We analyzed nuclear ITS and chloroplast ndhF sequence data from 68 accessions of Berberis s.l. The results support the monophyly of Berberis s.l., but compound‐leaved Berberis are shown to be paraphyletic. The analysis supports Berberis higginsae, a member of North American B . sect. Horridae, as sister to all other Berberis species . Our results, interpreted in the light of fossil evidence, suggest a North American origin of Berberis s.l., but the area of origin of the simple‐leaved group remains uncertain.